Regulasi Emosi dan Subjective Well-Being pada Remaja di PPSA Woro Wiloso Salatiga - Maleke, Ekaristi Gratia; Soetjiningsih, Christiana Hari (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Physical, cognitive, socio-emotional changes and the emergence of various problems that commonly occur during adolescence can have an effect on decreasing subjective well-being. This condition may also occur in teenagers living in orphanages. The aim of this research is to determine the relationship between emotion regulation and subjective well-being among adolescent who live in orphanage. This research uses a quantitative approach with a correlation design. Participant in this research were 102 adolescent using saturated sampling techniques. The emotion regulation research measurement using The Emotion Regulation Questionnaire (ERQ) and the research subjective well-being measurement for life satisfaction is the Satisfaction With Life Scale (SWLS) and for positive and negative affect components using Scale of Positive And Negative Experience (SPANE). The research data analysis method uses the product moment correlation test from Karl Pearson's. The research results show that there is a significant positive relationship between emotion regulation and subjective well-being (r = 0.489, sig. = 0.001). This shows that emotion regulation is one of the factors related to increasing subjective well-being among teenagers who live in an orphanage.